Mineral powder adhesive, titanium extraction tailing curing material, preparation method of mineral powder adhesive and titanium extraction tailing curing material, and sintered brick

By mixing and forming and roasting the titanium-elevated tailings with coal with a specific ratio of ore powder adhesive, the problem of failure to successfully produce sintered bricks is solved, and sintered bricks with high strength and good stability are achieved. Production, meets national standards and has wide application value.

CN119191854AActive Publication Date: 2024-12-27PANGANG GRP ENG TECH
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411372777.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

At present, there is no method to successfully produce titanium-elevated tailslag into sintered brick products, and it has failed to effectively utilize a large amount of titanium-elevated tailslag, and the quality of the building materials produced has failed to meet national standards.

Method used

A mineral powder binder is adopted, including 65~75 wt% lignin-based polymer, 15~20 wt% calcium carbonate, 2~3 wt% boric acid, 5~10 wt% magnesium chloride, 1 ~3 wt% of degumming agent and 0.3~1 wt% of humate, and then molded and calcined with titanium-enhancing tailslag and coal, the titanium-enhancing tailslag curing materials and sintered bricks are prepared with high strength and stability. .

Benefits of technology

The production of titanium-enhancing tailslag cured materials and sintered bricks with small usage, high strength and good stability has been achieved. The obtained products meet the national standards of GBT5101-2017, have good dimensional consistency and appearance quality, and are suitable for engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the fields of building material production, energy conservation, environmental protection and solid waste utilization, in particular to a mineral powder adhesive, a titanium extraction tailing curing material, a preparation method of the mineral powder adhesive and a sintered brick. The mineral powder adhesive provided by the invention can adhere the titanium extraction tailings into a curing material, the dosage is small, the amount of the titanium extraction tailings capable of being cured is large, and the obtained titanium extraction tailings curing material is high in strength and good in stability. Tests show that the mineral powder adhesive provided by the invention is used for preparing the titanium extraction tailings into sintered bricks, and the obtained sintered bricks meet the GBT5101-2017 national standard, are small in dimensional deviation, good in appearance and high in compressive strength, and have great popularization and application values at home and abroad.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of building material production, energy conservation and environmental protection, and solid waste utilization, and specifically to a mineral powder adhesive, a titanium-extracting tailing solidification material, a preparation method thereof, and a sintered brick. Background Art

[0002] The characteristics of titanium slag have a great impact on the production of building materials from titanium slag. How to successfully develop a method to produce sintered bricks using titanium slag, so that the huge amount of titanium slag can be effectively utilized each year and applied to engineering projects, with quality meeting national standards and achieving good results, has become a topic that needs to be studied and solved urgently. At present, there is no method to produce sintered bricks from Panzhihua Iron and Steel Titanium slag. Summary of the invention

[0003] In view of this, the technical problem to be solved by the present invention is to provide a mineral powder adhesive, a titanium extraction tailings solidification material and a preparation method thereof and a sintered brick. The mineral powder adhesive provided by the present invention can bond the titanium extraction tailings into a solidified material with a small amount, and can solidify a large amount of titanium extraction tailings. The obtained titanium extraction tailings solidification material has high strength and good stability.

[0004] The present invention provides a mineral powder adhesive, comprising:

[0005] 65-75 wt% of lignin-based polymer;

[0006] 15-20 wt% calcium carbonate;

[0007] 2~3 wt% boric acid;

[0008] 5-10 wt% magnesium chloride;

[0009] 1~3 wt% degumming agent;

[0010] and 0.3~1 wt% humate.

[0011] Preferably, the mineral powder adhesive provided by the present invention comprises:

[0012] 68-72 wt% lignin-based polymer;

[0013] 16-18 wt% calcium carbonate;

[0014] 2~3 wt% boric acid;

[0015] 7-9 wt% magnesium chloride;

[0016] 1~3 wt% degumming agent;

[0017] and 0.4~0.6 wt% humate.

[0018] The mineral powder adhesive provided by the present invention comprises a lignin-based macromolecular polymer, which can give the mineral powder adhesive good dispersibility, adhesion, chelation and complexation properties. The lignin-based macromolecular polymer of the present invention is calcium sulfonate.

[0019] The mineral powder adhesive provided by the present invention includes a degumming agent, which can reduce the contact between the surface active components of the mineral powder and water and improve the bonding effect. The degumming agent of the present invention is sodium bicarbonate.

[0020] The mineral powder adhesive provided by the present invention includes humate, which is compounded with other components in the mineral powder adhesive of the present invention to improve the hydrophilicity of the mixture and increase the forming rate. The humate described in the present invention is humate.

[0021] The mineral powder adhesive provided by the present invention also includes calcium carbonate, boric acid and magnesium chloride, wherein the calcium carbonate has a retarding effect and can improve the hardness and density of the solidified material; the boric acid can improve the viscosity, accelerate the solidification time, and enhance the strength of the solidified material; the magnesium chloride has a strong bonding property and is helpful for the processing and molding of mineral powder that is not easy to bond.

[0022] The mineral powder adhesive of the present invention is prepared by mixing the above-mentioned components at room temperature. Through the joint action of the components, it has the characteristics of small dosage, high strength and good stability in the molding and bonding of solid slag materials such as iron slag, phosphate ore powder, lead-zinc ore powder, titanium tailings, steel slag, etc.

[0023] In certain embodiments of the present invention, the mineral powder binder provided by the present invention comprises:

[0024] 65-75 wt% calcium sulfonate;

[0025] 15-20 wt% calcium carbonate;

[0026] 2~3 wt% boric acid;

[0027] 5-10 wt% magnesium chloride;

[0028] 1-3 wt% sodium bicarbonate;

[0029] and 0.3~1 wt% humate.

[0030] In certain embodiments of the present invention, the mineral powder binder provided by the present invention comprises:

[0031] 68-72 wt% calcium sulfonate;

[0032] 16-18 wt% calcium carbonate;

[0033] 2~3 wt% boric acid;

[0034] 7-9 wt% magnesium chloride;

[0035] 1-3 wt% sodium bicarbonate;

[0036] and 0.4~0.6 wt% humate.

[0037] The present invention also provides a titanium extraction tailings solidification material, which is prepared from raw materials including the following components:

[0038] Extract titanium tailings;

[0039] The mineral powder binder described in any of the above technical solutions;

[0040] coal.

[0041] The present invention adopts the mineral powder binder described in any of the above technical solutions, and can prepare a large amount of titanium tailings into a solidified material with a small amount of binder, and the prepared solidified material has high strength and good stability. Specifically, the titanium tailings solidified material provided by the present invention is prepared from raw materials including the following components, in parts by weight: 80-90 parts of titanium tailings; 1-6 parts of the mineral powder binder; 1-6 parts of coal. Preferably, the titanium tailings solidified material is prepared from raw materials including the following components, in parts by weight: 80-85 parts of titanium tailings; 2-5 parts of the mineral powder binder; 2-5 parts of coal. More preferably, the titanium tailings solidified material is prepared from raw materials including the following components: 83-85 parts of titanium tailings; 2-4 parts of the mineral powder binder; 3-5 parts of coal.

[0042] The specific components of the titanium-extracting tailings used in the titanium-extracting tailings solidified material provided by the present invention will affect the performance of the finally obtained solidified material. The titanium-extracting tailings preferably include the following components by weight:

[0043] TiO2: 10.00%~15.00%;

[0044] Cl ion: 2.00%~4.00%;

[0045] CaO: 24.00%~26.00%;

[0046] Fe2O3: 0.50%~1.00%;

[0047] K2O: 0.10%~0.30%;

[0048] MgO: 7.00%~10.00%;

[0049] MnO: 0.50%~1.00%;

[0050] Na2O: 0.10%~0.50%;

[0051] SiO2: 24.00%~26.00%;

[0052] Al2O3: 10.00%~15.00%;

[0053] The balance is water.

[0054] In certain embodiments of the present invention, the titanium extraction tailings preferably include the following components by weight:

[0055] TiO2: 13.00%~15.00%;

[0056] Cl ion: 2.50%~3.50%;

[0057] CaO: 25.00%~27.00%;

[0058] Fe2O3: 0.60%~1.00%;

[0059] K2O: 0.10%~0.30%;

[0060] MgO: 8.00%~9.00%;

[0061] MnO: 0.50%~0.80%;

[0062] Na2O: 0.10%~0.30%;

[0063] SiO2: 24.00%~26.00%;

[0064] Al2O3: 12.00%~14.00%;

[0065] The balance is water.

[0066] The particle size of the titanium-extracting tailings and the mineral powder binder used in the titanium-extracting tailings solidification material provided by the present invention is no more than 400 mesh; the particle size of the coal is no more than 2 mm. Preferably, the particle size of the titanium-extracting tailings is no more than 400 mesh; the particle size of the mineral powder binder is no more than 400 mesh; the particle size of the coal is no more than 2 mm. The moisture content of the titanium-extracting tailings, mineral powder binder and coal powder used in the titanium-extracting tailings solidification material provided by the present invention cannot be greater than 3%.

[0067] The present invention also provides a method for preparing the titanium-extracting tailings solidified material described in any of the above technical solutions, comprising the following steps: mixing the titanium-extracting tailings, mineral powder binder, coal and water, and roasting to obtain the titanium-extracting tailings solidified material.

[0068] Specifically, the present invention mixes titanium tailings, mineral powder binder and coal, adds water thereto and continues mixing, then forms, dries the formed blank, and then roasts it to obtain a titanium tailings solidified material. The weight ratio of the titanium tailings, mineral powder binder, coal and water used in the present invention is (80~90): (2~5): (3~6): (7~11), preferably (80~85): (2~5): (2~5): (7~11), and more preferably (83~85): (2~4): (3~5): (8~10). The forming of the present invention can be carried out according to the desired product. The drying temperature of the present invention is 100℃~150℃, and the drying time is 20 h~28 h. The calcination temperature of the present invention is 900°C~1100°C, and the calcination time is 3~5 h; preferably, the calcination is a two-stage calcination, specifically: heating to 500°C~700°C at a heating rate of 1°C / min~2°C / min, keeping warm for 1 h~1.5 h, and then heating to 900°C~1100°C for calcination for 3 h~5 h.

[0069] The present invention also provides a sintered brick, which is obtained from the titanium tailings solidified material described in any of the above technical solutions. Specifically, titanium tailings, mineral powder binder, coal and water are mixed, pressed into shape, and roasted to obtain the titanium tailings solidified material. More specifically, titanium tailings, mineral powder binder and coal are mixed, water is added thereto and the mixture is continued to be mixed, and then pressed into shape, the pressed bricks are dried, and then roasted to obtain sintered bricks. The weight ratio of the titanium tailings, mineral powder binder, coal and water used in the present invention is the same as that in the preparation method of the titanium tailings solidified material, and will not be repeated. The drying and roasting in the present invention are also the same as those in the preparation method of the titanium tailings solidified material, and will not be repeated. The pressing pressure of the present invention is 15 kN~25 kN, preferably 20 kN. In certain embodiments of the present invention, the obtained bricks are free of cracks, and the dimensional deviation is not greater than 2 mm; the moisture content of the bricks after drying is not greater than 1%.

[0070] The present invention provides a mineral powder adhesive, a titanium extraction tailings solidification material, a preparation method thereof, and a sintered brick. The mineral powder adhesive provided by the present invention can bond the titanium extraction tailings into a solidified material, with a small amount of use, a large amount of titanium extraction tailings that can be solidified, and the obtained titanium extraction tailings solidified material has high strength and good stability. Experiments show that the mineral powder adhesive provided by the present invention is used to make titanium extraction tailings into sintered bricks, and the obtained sintered bricks meet the national standard GBT5101-2017, have small dimensional deviation, good appearance, high compressive strength, and have great promotion and application value at home and abroad. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1This is a diagram showing the appearance of a sintered brick obtained in Example 1 of the present invention;

[0072] Figure 2 The second figure is the appearance of the fired brick obtained in Example 1 of the present invention;

[0073] Figure 3 Three figures showing the appearance of the fired brick obtained in Example 1 of the present invention;

[0074] Figure 4 This is a diagram of the internal state of the sintered brick obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0075] The present invention discloses a mineral powder adhesive, a titanium tailings solidification material, a preparation method thereof, and a sintered brick. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0076] The present invention will be further described below in conjunction with embodiments:

[0077] Example 1

[0078] (1) Raw material preparation

[0079] According to the formula of titanium tailings sintered bricks, titanium tailings, mineral powder binder and coal powder are conveyed to the mixing barrel through a belt conveyor and fully mixed. After mixing, water is added in proportion and fully mixed for 20 minutes to obtain a mixed material. (The moisture content of titanium tailings, mineral powder binder and coal powder cannot be greater than 3%; the particle size of titanium tailings and mineral powder binder cannot be greater than 400 mesh; the particle size of coal powder cannot be greater than 2 mm.)

[0080] The formula of titanium tailings sintered brick is shown in Table 1 (based on 100 kg of raw materials as 1 component):

[0081] Table 1

[0082]

[0083] Among them, the composition of titanium tailings is shown in Table 2:

[0084] Table 2

[0085]

[0086] The formula of mineral powder binder is shown in Table 3:

[0087] Table 3

[0088]

[0089] (2) Molding

[0090] The mixed material is conveyed to the silo by a belt conveyor and pressed into shape by a brick making machine. The material distribution is required to be uniform, the pressure of the brick making machine is 20 kN; the bricks are formed without cracks and the size deviation is no more than 2 mm.

[0091] (3) Drying

[0092] After the bricks are formed, they are transported to the drying equipment for drying. The hot air temperature is 150 degrees Celsius and the drying time is 24 hours. If the moisture content is not more than 1%, it is qualified.

[0093] (4) Calcination

[0094] After the bricks are dried, they are put into a baking furnace for firing. The heating rate is 1 degree Celsius per minute. When the temperature reaches 600 degrees Celsius, it is kept warm for 1 hour, then the temperature is raised to 1000 degrees and fired for 3 hours. At the end, sintered bricks are obtained.

[0095] (5) Quality inspection

[0096] ①Dimensional deviation

[0097] The dimensions of ordinary fired bricks are 240 mm in length, 115 mm in width and 53 mm in thickness. For specific dimension deviation requirements, please refer to the national standard GBT5101-2017.

[0098] The sintered bricks obtained in Example 1 of the present invention were inspected for size and quality, and the results are shown in Table 4:

[0099] Table 4

[0100]

[0101] ②Appearance quality

[0102] The appearance quality inspection requirements of sintered bricks refer to the national standard GBT5101-2017. The appearance and internal state of the sintered bricks obtained in Example 1 of the present invention are as follows: Figure 1~Figure 4 As shown, Figure 1 This is a diagram showing the appearance of the sintered brick obtained in Example 1 of the present invention. Figure 2 The second figure is the appearance of the fired brick obtained in Example 1 of the present invention. Figure 3 These are three pictures showing the appearance of the fired brick obtained in Example 1 of the present invention. Figure 4 This is a diagram of the internal state of the sintered brick obtained in Example 1 of the present invention. Figure 1~Figure 3 Among them, the fired brick No. 1 is the fired brick after the above-mentioned (3) drying, and the fired bricks No. 2 and No. 3 are the fired bricks after the above-mentioned (4) firing.

[0103] The appearance quality results of the sintered bricks obtained in Example 1 of the present invention are shown in Table 5:

[0104] Table 5

[0105]

[0106] ③ Strength results

[0107] Compressive strength MU10 strength grade requirements refer to the national standard GBT5101-2017. : Average compressive strength Not less than 10 MPa, fk not less than 6.5 MPa.

[0108] The strength of the sintered brick obtained in Example 1 of the present invention was tested, and the results are shown in Table 6, which meet the MU10 standard strength.

[0109] Table 6

[0110]

[0111] In Table 6, sample number 1 (drying) corresponds to Figures 1 to 3 The sintered brick of sample No. 1 after the drying in (3) above, the corresponding brick of sample No. 2 (fired) is Figures 1 to 3 The sintered brick of sample No. 2 after the above (4) calcination, the corresponding sample No. 3 (calcined) is Figures 1 to 3 The sintered brick No. 3 is sintered after the above-mentioned (4) firing.

[0112] ④ Weathering resistance index (not tested according to the specification)

[0113] ⑤ No frost or lime cracking was found on the bricks.

[0114] ⑥Radioactivity detection complies with GB6566 standard.

[0115] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A mineral powder adhesive, characterized in that: include: 65-75 wt% of lignin-based polymer; 15-20 wt% calcium carbonate; 2~3 wt% boric acid; 5-10 wt% magnesium chloride; 1~3 wt% degumming agent; and 0.3~1 wt% humate.

2. The mineral powder binder according to claim 1, characterized in that: include: 65-75 wt% calcium sulfonate; 15-20 wt% calcium carbonate; 2~3 wt% boric acid; 5-10 wt% magnesium chloride; 1-3 wt% sodium bicarbonate; and 0.3~1 wt% humate.

3. The mineral powder binder according to claim 1, characterized in that: include: 68-72 wt% calcium sulfonate; 16-18 wt% calcium carbonate; 2~3 wt% boric acid; 7-9 wt% magnesium chloride; 1-3 wt% sodium bicarbonate; and 0.4~0.6 wt% humate.

4. A titanium tailings solidification material, characterized in that: It is prepared from raw materials including the following components: Extract titanium tailings; The mineral powder binder according to any one of claims 1 to 3; coal.

5. The titanium extraction tailings solidified material according to claim 4, characterized in that: The preparation method is based on the following components: 80~90 parts of titanium extraction tailings; 2 to 5 parts of the mineral powder binder; 3~6 portions of coal.

6. The titanium extraction tailings solidified material according to claim 4, characterized in that: The titanium extraction tailings include the following components by weight: TiO2: 10.00%~15.00%; Cl ion: 2.00%~4.00%; CaO: 24.00%~26.00%; Fe2O3: 0.50%~1.00%; K2O: 0.10%~0.30%; MgO: 7.00%~10.00%; MnO: 0.50%~1.00%; Na2O: 0.10%~0.50%; SiO2: 24.00%~26.00%; Al2O3: 10.00%~15.00%; The balance is water.

7. The titanium extraction tailings solidified material according to claim 4, characterized in that: The particle size of the titanium extraction tailings is not greater than 400 mesh; The particle size of the mineral powder binder is not greater than 400 mesh; The particle size of the coal is not greater than 2 mm.

8. The method for preparing the titanium extraction tailings solidified material according to any one of claims 4 to 7, characterized in that: The following steps are involved: The titanium-extracting tailings, mineral powder binder, coal and water are mixed and formed, and then roasted to obtain the titanium-extracting tailings solidified material.

9. The preparation method according to claim 8, characterized in that: The weight ratio of the titanium extraction tailings, mineral powder binder, coal and water is: (80-90): (2-5): (3-6): (7-11).

10. A fired brick, characterized in that: The titanium-extracting tailings solidified material is obtained from any one of claims 4 to 7.

Citation Information

Patent Citations

  • Water soluble effervescence composition and method of making the same

    CN101423443A

  • Method for preparing pelletized calcium carbide raw material by carbon raw material and quick lime mixed molding

    CN107010626A

  • Compounds useful as modulators of trpm8

    CN108473484A

  • Sintered brick and preparation method thereof

    CN109081681A

  • Preparation method of nano magnesium borate / lignin composite material

    CN110003676A